Отчий край: роман / Константин Седых - Седых Константин Федорович (Сибириада, 2022)
Экземпляры: ф.8 (20230414) / Инвентарный номер: 63335 / Цена: / Сис.шифр: 84(2Рос=411.2)6-4 / Авт.знак: С 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-442